1986
DOI: 10.1530/jrf.0.0770239
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of hCG, hydroxysteroids and interstitial fluid on rat Leydig cell steroidogenesis in vitro

Abstract: Summary. Rat

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1987
1987
1995
1995

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 6 publications
2
15
1
Order By: Relevance
“…In our study, the optimum 22a-hydroxycholesterol concentration required to elicit the maximum rates of steroido¬ genesis (100-200 pmol l-1 depending on the steroid and on the nature of the lobule) was comparable to that required for rat Leydig cells (100 pmol 1" \ Risbridger et al, 1986 (Hall et al, 1969;Cooke et al, 1972) and that rat Sertoli cells cannot convert pregnenolone to progesterone (Wiebe et al, 1988 Kime (1978) and Cuevas and Callard (1992) (Sourdaine et al, 1990 (Dobson and Dodd, 1977), as observed in Torpedo marmorata and T. ocellata by Fasano et al (1989). This highlights the importance of the contribution of testicular paracrine mechanisms and, in particular, the effects of germ cells for the control of steroid production.…”
Section: Introductionsupporting
confidence: 48%
“…In our study, the optimum 22a-hydroxycholesterol concentration required to elicit the maximum rates of steroido¬ genesis (100-200 pmol l-1 depending on the steroid and on the nature of the lobule) was comparable to that required for rat Leydig cells (100 pmol 1" \ Risbridger et al, 1986 (Hall et al, 1969;Cooke et al, 1972) and that rat Sertoli cells cannot convert pregnenolone to progesterone (Wiebe et al, 1988 Kime (1978) and Cuevas and Callard (1992) (Sourdaine et al, 1990 (Dobson and Dodd, 1977), as observed in Torpedo marmorata and T. ocellata by Fasano et al (1989). This highlights the importance of the contribution of testicular paracrine mechanisms and, in particular, the effects of germ cells for the control of steroid production.…”
Section: Introductionsupporting
confidence: 48%
“…The presence of steroidogenic stimulatory activity in interstitial fluid has been previously reported (Sharpe & Cooper, 1984;Rommerts et al, 1986;Risbridger et al, 1986) and it has been shown that the stimulatory activity increases 20 days after the induction of unilateral cryptorchidism (Sharpe et al, 1986). The present study clearly demonstrates that the steroidogenic stimulatory activity results in parallel and linear dose-response lines for interstitial fluid from scrotal and abdominal testes.…”
Section: Discussionmentioning
confidence: 75%
“…The testes were then excised and interstitial fluid was collected by allowing the testes to drain (from a small incision in the caudal end of the testes) for 16 h at 4°C. The recovered fluid was centrifuged and treated with charcoal before storage at -20°C as described previously (Risbridger et a!, 1986). The concentrations of testosterone and progesterone in aliquants of each of these samples were also determined by radioimmunoassay (Risbridger et a!, 1986 (Finney, 1971 (Kerr & Sharpe, 1985) by scoring the number of points falling over Leydig cells and the lymphatic space expressed as a percentage of the total number of points over each microscopic field: 133 sections (all from different blocks) from all testes were examined in which 906 randomly selected areas were scored using 399 546 test points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports suggested a possible interaction in Leydig cells-semiferous tubules (intersti tial fluid) damaged by cryptorchidism. Risbridger et al [30] suggested that interstitial fluid acts to stimulate the conversion of cholesterol to pregnenolone. When choles terol side-chain cleavage enzymatic activity is sup pressed by high temperature in the abdomen, cholesterol should be restored in Leydig cell membranes, especially in mitochondria.…”
Section: Days After Treatmentmentioning
confidence: 99%